Creating arts and crafting positively predicts subjective wellbeing - Keyes, Helen; Gradidge, Sarah; Forwood, Suzanna Elizabeth; Gibson, Nic; Harvey, Annelie; Kis, Evelin; Mutsatsa, Karen; Ownsworth, Rachel; Roeloffs, Shyanne; Zawisza, Magdalena (Frontiers in Public Health, 2024)
This study explored whether engagement with Creating Arts and Crafting (CAC) predicted subjective wellbeing and loneliness, above and beyond known sociodemographic predictors. Methods: Secondary data from 7,182 adults living in England from the Taking Part Survey (a 2019-2020 UK household survey of culture and sport participation) were analyzed. Hierarchical Linear regressions were used to explore the predictive effect of engagement with CAC on aspects of subjective wellbeing (anxiety, happiness, life satisfaction and a sense that life is worthwhile) and loneliness. Covariates included gender, Index of Multiple Deprivation (IMD), age group, health and employment status. Results: Engaging in CAC significantly predicted increased life satisfaction, a sense that life is worthwhile and happiness, above and beyond known sociodemographic predictors. Conclusions: Our study provides support for the wellbeing benefits of engagement with creating arts and crafting, and we suggest that this will be a useful tool at a public health level, noting that relative accessibility and affordability creating arts and crafting.